Effect of breathing pattern on arm coordination symmetry in front crawl - Seifert, L.; Chehensse, A.; Tourny-Chollet, C.; Lemaitre, F.; Chollet, D. (The Journal of Strength and Conditioning Research, 2008)
This study analyzed the relationship between breathing pattern and arm coordination symmetry in 11 expert male swimmers who performed the front crawl at their 100-m race pace using seven randomized breathing patterns. Two indexes of coordination (IdCP and IdCNP) and a symmetry index (SI) based on the difference of IdCP - IdCNP were calculated. IdCP calculated the lag time between the beginning of arm propulsion on the nonpreferential breathing side and the end of arm propulsion on the preferential breathing side; IdCNP did the converse. The IdCP and IdCNP comparisons and the SI showed coordination asymmetries among the seven breathing patterns. Specifically, breathing to the preferential side led to an asymmetry, in contrast to the other breathing patterns, and the asymmetry was even greater when the swimmer breathed to his nonpreferential side. These findings highlight the effect of breathing laterality in that coordination was symmetric in patterns with breathing that was bilateral, axed (as in breathing with a frontal snorkel), or removed (as in apnea). One practical application is that arm coordination asymmetry can be prevented or reduced by using breathing patterns that balance the coordination.